The Distinctive Features of Diffusion Interaction of Copper and Molybdenum under Pressure Welding Through the Layers Modified by Ion-Beam Processing - Mazanko, V.F.; Kharchenko, H.K.; Hanieiev, T.R.; Novomlynets, O.O.; Zavalna, I.V. (Металлофизика и новейшие технологии, 2015)
The process of diffusion welding of copper with molybdenum in the vacuum through the layers modified by ion-beam processing is investigated. The distinctive features of diffusion interaction of copper and molybdenum are determined using the radioactive tracer technique. The possibility of substantial influence of changing the critical parameters of the mode of ion-beam processing of surface layer of the welded material on the sizes of interaction zone and mechanical properties of the joint weld is shown. Expediency of previous modification of molybdenum surface with copper in the process of diffusion welding of copper with the molybdenum in the vacuum is established.